Trichoderma spp. como potenciais agentes de controle biológico para podridão vermelha ocasionada por Colletotrichum falcatum em resíduos de pós-colheita de cana-de-açúcar - Oliveira, Guilherme Pereira de (2020)
In the last years, red rot disease caused by Colletotrichum falcatum has caused a lot of damage to the sugarcane crop, affecting the yield. The main problem is that the pathogen remains in the crop residues and multiplies, being an important source of inoculum for the next crop year. Alternatives that may reduce C. falcatum inoculum in post-harvest residues are a great tool to be integrated into the management of the disease in sugarcane. Thus, the aim of this study was to evaluate the potential of products based on Trichoderma spp. as biological control agents against C. falcatum in post-harvest sugarcane residues. The experiment was conducted in a commercial sugarcane production area located in João Pinheiro, MG, Brazil. The experimental design in randomized blocks with three treatments (control and products based on Trichoderma asperellum and Trichoderma koningiopsis) and seven replicates was implemented after the first harvest in the cultivation area of the variety RB867515. Two collections of post-harvest residue samples were performed, an initial collection before application of products and, a second collection 30 days after the application of the treatments. qPCR technique was used to quantify the number of DNA copies of C. falcatum/μL in post-harvest residues. Analysis of deviance was performed under generalized linear model adjusted to Poisson distribution, and means were compared by Tukey test. The results of molecular quantification showed a significant reduction in the pathogen inoculum (p-value < 0.10) after application of treatments based on T. asperellum and T. koningiopsis. Since there was no statistical difference in the initial quantification of the pathogen, Abbott's formula was applied and the treatments with T. asperellum and T. koningiopsis showed efficacy of 9.73% and 47.79%, respectively, in reducing the growth of C. falcatum 30 days after application on post-harvest sugarcane residues. In summary, we demonstrate the efficacy of a single application of products based on T. asperellum and T. koningiopsis and their potential as a biocontrol agent for the C. falcatum population in post-harvest sugarcane residues. In addition, our study showed that the qPCR technique is a powerful molecular biology tool that can be used to evaluate the efficacy of biological control agents.